Finale Dehnung im Deutschen - Streck, Tobias (Universität, 2004)
Zusammenfassung: Final lengthening (or pre-boundary lengthening) means, that a syllable in the position directly before a prosodic boundary is longer pronounced than a phonotactic similar syllable in a position not before such a boundary. FL is a large effect at intonational-phrase- and utterance-boundaries, that exists in many languages. In this text an investigation with focus on the urban varieties of Hamburg and Mannheim is presented. The aim of the work is to find out, if there is evidence for utterance-final lengthening in these regional varieties, if there is possibly a regional variation in FL and if the phenomenon plays a role in the organization of turntaking.
urn:nbn:de:bsz:25-opus-14910
Keywords: finale Dehnung; Mannheim; Hamburg; Äußerungseinheiten; Spontansprache; final lengthening; utterance; phrase; turntaking; (local)masterThesis; Gesprochene Sprache; Gliederungssignal; Dehnung; Prosodie; Stadtmundart; Sprecherwechsel; Phonetik; Online-Ressource